Pain Neuroscience Education: State of the Art and Application in Pediatrics - Hannah Robins; Victoria Perron; Lauren C. Heathcote; Laura E. Simons (MDPI AG, 2016)
Chronic pain is a widespread problem in the field of pediatrics. Many interventions to ameliorate pain-related dysfunction have a biobehavioral focus. As treatments for chronic pain (e.g., increased movement) often stand in stark contrast to treatments for an acute injury (e.g., rest), providing a solid rationale for treatment is necessary to gain patient and parent buy-in. Most pain treatment interventions incorporate psychoeducation, or pain neuroscience education (PNE), as an essential component, and in some cases, as a stand-alone approach. The current topical review focuses on the state of pain neuroscience education and its application to pediatric chronic pain. As very little research has examined pain neuroscience education in pediatrics, we aim to describe this emerging area and catalyze further work on this important topic. As the present literature has generally focused on adults with chronic pain, pain neuroscience education merits further attention in the realm of pediatric pain in order to be tailored and implemented in this population.